Alles was irgendwie nützt - All what is somehow useful (Karakul Circulations: Colonial Economies and the Un_Making of Disciplinary Knowledges in Germany and Namibia, 1905)
Video created with Uni Halle materials.
Keywords: Archival materials; Animal breeding; Agriculture; Karakul sheep; Germany; Halle; Karakul Farming; Karakul Sheep Industry